2015
DOI: 10.1182/blood-2015-04-638494
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling induces transcription, spatial proximity, and translocation of fusion gene partners in human hematopoietic cells

Abstract: Key Points• Wnt/b-catenin signaling increases ETO and Runx1 transcription in human hematopoietic progenitors.• Wnt/b-catenin signaling enhances spatial proximity of ETO and RUNX1 genes and induces the generation of a recurrent translocation event.Chromosomal translocations are frequently associated with a wide variety of cancers, particularly hematologic malignancies. A recurrent chromosomal abnormality in acute myeloid leukemia is the reciprocal translocation t(8;21) that fuses RUNX1 and ETO genes. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…Our case supports the hypothesis that BCL7A deletion induces abnormal Wnt/β-catenin signaling, enhancing the potential for a chromosomal aberration and its persistence in our patient [510]. Loss of the tumor suppressor BCL7A may cooperate with AID activity in disease progression by causing aberrant cell cycle regulation [1].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Our case supports the hypothesis that BCL7A deletion induces abnormal Wnt/β-catenin signaling, enhancing the potential for a chromosomal aberration and its persistence in our patient [510]. Loss of the tumor suppressor BCL7A may cooperate with AID activity in disease progression by causing aberrant cell cycle regulation [1].…”
supporting
confidence: 86%
“…The AID gene, located on chromosome 12p13, is associated with genomic instability and ensuing oncogenesis in various human malignancies including CML, AML, and ALL [345]. AID has several non-immunoglobulin targets, including PAX5 and BCL7A [36]; PAX5 can induce TKI resistance and CML progression via AID upregulation [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast as early-replicating loci are more interactive (Brown et al, 2008;Lieberman-Aiden et al, 2009), and therefore DNA breaks occurring in regions replicating in early S-phase are more likely to result in trans translocations. Our model is supported by studies that show copy number aberration breakpoints generally have the same replication timing and interact long-range (De and Michor, 2011), and that translocation partners are required to be within the same spatial area, transcription (Ugarte et al, 2015) or replication factory (Coll- Bastus et al, 2015), before translocation can occur. A pertinent example for prostate cancer is the TMPRSS2-ERG gene fusion that occurs in ~50-80% of all prostate cancer (Tomlins et al, 2005).…”
Section: Discussionsupporting
confidence: 59%
“…Dependent on tissue context and developmental stage, different signaling pathways modulate Runx1 expression, including the retinoic acid (Tanaka et al, 1995), Notch (Burns et al, 2005), and more recently the Wnt/b-catenin signaling cascade (Wu et al, 2012;Wang et al, 2013;Ugarte et al, 2015). Interestingly, it has been observed that Tcf7, a member of the T-cell factor/lymphoid enhancing factor (TCF/LEF) family of proteins known to mediate Wnt/b-catenin signaling in the nucleus (Clevers and van de Wetering, 1997), is required for a transcriptional program in a mouse EML (Erythroid, Myeloid, and Lymphocytic) multipotential hematopoietic precursor cell-line to produce the alternative P2-proximal Runx1 mRNA isoform (Wu et al, 2012).…”
mentioning
confidence: 99%